Method and Mapping of Trust and Trustworthiness in Agroindustry Logistic and Supply Chain: a Systematic Review - Rindra Yusianto; Sambas Sundana; Marimin Marimin; Taufik Djatna (International Journal of Supply Chain Management, 2020)
This paper proposes trust and trustworthiness as a novel approach in agroindustry logistic and supply chain. The objective of this article is to analyze the existing methods and approaches for trust and trustworthiness to develop a new framework in agroindustry logistics and the supply chain from shipment planning, routing and scheduling, shipping execution and inventory control processes. The author reviewed and synthesized 84 scientific articles which were published between 2004 and 2019. The reviewed articles were categorized into contract, competencies, goodwill, and performance trust and trustworthiness. The potentials identified for future research were the importance role of management in maintaining trust and trustworthiness in the supply chain system. Most previous authors have applied an approach of interaction and impact on collaborative relationship and performance in supply chains. The dominant methods we found in literature were contractual and impact on relationship quality. Most of the literature focuses on managing trust relationships and there is a lack of discussion about the relationship of trust in shipment planning, routing and scheduling, shipping execution and inventory control. The contribution of this paper was mapping the method in relationship of trust, trustworthiness and develop new framework. This paper developed and suggested a new framework for maintaining trust and trustworthiness in the agroindustry logistic and supply chain model.